Investigation and management of Wilson's disease: a practical guide from the British Association for the Study of the Liver. (June 2022) - Shribman, Samuel; Marjot, Thomas; Sharif, Abubakar; Vimalesvaran, Sunitha; Ala, Aftab; Alexander, Graeme; Dhawan, Anil; Dooley, James; Gillett, Godfrey T; Kelly, Deirdre; McNeill, Alisdair; Warner, Thomas T; et al.
Summary: Wilson's disease is an autosomal-recessive disorder of copper metabolism with hepatic, neurological, psychiatric, ophthalmological, haematological, renal, and rheumatological manifestations. Making a diagnosis can be challenging given that no single test can confirm or exclude the disease, and diagnostic delays are common. Treatment protocols vary and adverse effects, including paradoxical neurological worsening, can occur. In this Review, we provide a practical guide to the diagnosis of Wilson's disease. We include recommendations on indications for testing, how to interpret results, and when additional investigations are required. We also cover treatment initiation, ideally under the guidance of a specialist centre for Wilson's disease, and the principles behind long-term management. This guidance was developed by a multidisciplinary group of Wilson's disease experts formed through the British Association for the Study of the Liver. The guidance has been endorsed by the British Society of Gastroenterology and approved by the Association of British Neurologists.